Penerapan Metode Six Sigma DMAIC dengan Pendekatan Failure Mode and Effect Analysis pada Produk Roti Alfitra Bakerry - Ipal Rahmat Jaya; Agusyarif Rezka Nuha; La Ode Nashar (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
In the era of globalization, product quality plays a crucial role in meeting consumer demands and maintaining a company's competitiveness. This study aims to identify the causes of product defects and provide improvement recommendations in the production process of Alfitra Bakery using the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) methodology combined with Failure Mode and Effect Analysis (FMEA). The research was conducted through field observations and interviews at Alfitra Bakery, Gorontalo, focusing on two dominant types of defects: scorched (burnt) bread and under-expanded bread. The scorched defect was found to have a Risk Priority Number (RPN) of 490, while the under-expansion defect had an RPN of 210. The main factors contributing to scorched bread include prolonged baking time, inaccurate monitoring by workers, and manual calculation of baking time. Recommended improvements involve increasing employee supervision during baking, conducting regular briefings before production, and installing automatic timers to control baking time. Meanwhile, under-expanded bread was caused by inadequate yeast in the dough, poor employee precision, excessive fermentation time, and unstable oven temperature. Recommendations for improvement include using a measuring tool for yeast dosage, improving fermentation time management, employee training, and using ovens with automated temperature control systems. These recommendations aim to reduce defect rates and improve product quality consistency. The integration of Six Sigma and FMEA proves effective in systematically identifying and resolving quality issues in the bakery industry.